VD_FINDINFO Jug / 2016 / 262 vom 19. April 2016 - VD Tribunal cantonal (2016)
FICTION DE LA NOTIFICATION, DÉCISION D'IRRECEVABILITÉ, ANNONCE D'APPEL | 399 al. 1 CPP (CH), 85 al. 4 CPP (CH), 91 CPP (CH)